2016
DOI: 10.1111/jvh.12662
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C infection and other drug‐related harms among inpatients who injected drugs in Turkey

Abstract: Hepatitis C virus (HCV) is easily spread among those who share drug injection equipment. Due to the ease of contraction and growing prevalence of HCV in Eastern Europe, the aims of this study focused on describing risky injection practices as well as the prevalence of HCV, HIV and hepatitis B virus (HBV) among people who inject drugs (PWID) who were admitted to public and private drug treatment centres in Turkey from 2012 to 2013. Other aims included identifying correlates of needle sharing and HCV infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…HIV testing is performed before every surgery, blood donation, and in premarital screening for every individual and also for registered sex workers. 7 Risk groups are sex workers, injection drug users, and men who have sex with men (MSM) 8,9 and these groups are screened routinely. HIV prevalence among MSM is high in Istanbul: a recent study reported 12.7%.…”
Section: Introductionmentioning
confidence: 99%
“…HIV testing is performed before every surgery, blood donation, and in premarital screening for every individual and also for registered sex workers. 7 Risk groups are sex workers, injection drug users, and men who have sex with men (MSM) 8,9 and these groups are screened routinely. HIV prevalence among MSM is high in Istanbul: a recent study reported 12.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the age group with the highest prevalence for HCV infection in the general population is 25 and above, but there is also an increase in prevalence in 50 years and above as well (29). In a study conducted with data from 22 AMATEM and several private clinics in Türkiye, HCV infection was detected in 47% of patients with intravenous substance use; and the majority of these patients consisted of teenagers and young adults (30). Another study conducted with substance addicts in the Eastern Anatolian region of Turkey showed that there were no patients with HCV infection below the age of 20, but 22% of those with an HCV infection were in the 20-29 years age range (22).…”
Section: Discussionmentioning
confidence: 99%
“… 8 - 11 Anti-HCV antibody mean was found as 1.1% in the studies conducted with general population in Turkey in previous years 12 whereas anti-HCV antibody prevalence was reported as 36% to 47% in studies conducted with the participation of PWID. 13 - 15…”
Section: Introductionmentioning
confidence: 99%